Technology Adoption under Fit Risk: What Should Development Project Donors and Managers Know?. (2015) - Parks, Moon; Bansal, Sangeeta; Zilberman, David
Abstract: While relevant and important in understanding technology adopters' behavior, pre-acquisition fit risk in development projects is rarely discussed in the economics and development communities. This paper attempts to introduce fit risk in the development context and examines how its presence affects adoption of new technologies in development project settings. It also analyzes the impact of risk-reduction marketing tools on project uptake rate and their efficient utilization.